Upaya Guru Kelas dalam Menanamkan Pendidikan Karakter Jujur Melalui Metode Bercerita di TK Kemala Bhayangkari Muara Bungo - Dea Febrianti; Muhiddinur Kamal; Junaidi Junaidi; M. Arif (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research is motivated by several problems that the author found at the Bhayangkari Muara Bungo Kindergarten, students often lie, every time they say a word, many children don't want to be honest, and also lie, if asked, many also answer by lying, children don't want to admit their mistakes, because children are afraid of being scolded. and are afraid of being punished by the teacher, therefore children are afraid to be more open or honest. The purpose of this research is to find out how class teachers try to instill honest character education through the method of telling stories to children at the Kemala Bhayangkari Muara Bungo Kindergarten. This research is descriptive qualitative field research (filed research). The research was located at Kemala Bhayangkari Muara Bungo Kindergarten. The key informants were the class teachers and the supporting informants were the study teachers and the school principal. This research technique is snowball sampling, and the data collection techniques for this research are observation, interviews and documentation. The results of this research show that class teachers and field teachers tell stories through the Sikancil & Simonyet fairy tale and the Honesty Cup because fairy tales, one of the intrinsic elements in fairy tales, is that they have a message or moral message. Fairy tales can really be used as social media that can shape a character. children because fairy tales have moral values that children can learn. Telling stories using puppets can improve children's pronunciation because it can attract students' attention so that students are happy and can easily understand what is being told and taught. Telling stories using picture media, students will be able to read the contents of the story by looking at the pictures shown by the teacher, telling stories using picture media, students will be more enthusiastic about listening to stories presented by the teacher, telling stories using picture media will help to clarify messages or events so that children pay more attention to the story being told.